2017
DOI: 10.3892/ol.2017.5700
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with the herbal formula Songyou Yin inhibits epithelial-mesenchymal transition in hepatocellular carcinoma through downregulation of TGF-β1 expression and inhibition of the SMAD2/3 signaling pathway

Abstract: It was previously reported that treatment with the herbal formula Songyou Yin (SYY) may serve a role in attenuating epithelial-mesenchymal transition (EMT). In the present study, the effect of treatment with SYY on transforming growth factor-β1 (TGF-β1)-induced EMT was investigated and the potential underlying molecular mechanisms were evaluated. MHCC97H cells were pretreated with SYY for 4 weeks and subsequently named MHCC97HSYY cells. Simultaneously, MHCC97H cells were cultured for 4 weeks without SYY and us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Endometrial cancer develops and progresses according to the changes in genetic and epigenetic mutations in several genes associated with cancer and dysregulated hormone levels ( 4 ). During the epithelial-mesenchymal transition (EMT) process, polarized epithelial cells become active and show mesenchymal characteristics, and the features of EMT include the increase of the N-cadherin mesenchymal marker, the decrease of the E-cadherin epithelial marker, and the attainment of fibroblast-like migratory and invasive phenotypes ( 5 ). As cancer treatment is constantly changing, gene therapy and targeted therapy have gained increasing attention ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Endometrial cancer develops and progresses according to the changes in genetic and epigenetic mutations in several genes associated with cancer and dysregulated hormone levels ( 4 ). During the epithelial-mesenchymal transition (EMT) process, polarized epithelial cells become active and show mesenchymal characteristics, and the features of EMT include the increase of the N-cadherin mesenchymal marker, the decrease of the E-cadherin epithelial marker, and the attainment of fibroblast-like migratory and invasive phenotypes ( 5 ). As cancer treatment is constantly changing, gene therapy and targeted therapy have gained increasing attention ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Metastasis is responsible for more than 90% of cancerassociated mortality. EMT is considered a fundamental step in the initiation of the metastatic cascade, in which process tumor cells lose epithelial polarity and acquire invasive properties [35]. Many cytokine factors have been associated with tumor invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…SYD is similar in composition to other prescriptions of Chinese herbal compounds. For example, Songyou Yin has been reported to inhibit tumor growth and prolong survival in nude mice bearing a human hepatocellular carcinoma xenograft with high metastatic potential (16,17), however its composition is unknown. It has been reported that SYD comprises two cruciferous vegetable species with some bioactive constituents that exhibit antitumor properties (4,18).…”
Section: Discussionmentioning
confidence: 99%